Enhanced influenza vaccination among healthcare personnel prevents cases despite community burden - Isaí Medina-Piñón; Magaly Padilla-Orozco; Lidia Mendoza-Flores; Elvira Garza-González; Raul G Salazar-Montalvo; Samantha Flores-Treviño; Adrián Camacho-Ortiz (Journal of Infection in Developing Countries)
Introduction: Influenza vaccination for healthcare personnel is not obligatory in Mexico, and compliance relies on promotion and persuasion. The objective of this study was to determine the impact of influenza vaccination compliance on the reduction of influenza and influenza-like illness among healthcare personnel throughout two consecutive influenza seasons.